Gas Hydrate Technology: Computational Modeling for the Hydrate Growth Stage - Ferreira Filho, Ivan Ramos (2021)
Within sustainable chemistry, gas hydrates are gaining prominence due to their innovative applications in different scientific and industrial contexts. The ability to understand and control its properties is crucial to the full development of hydrate-based technologies. In this context, based on the mathematical model published by Vlasov for methane hydrate formation, the present study seeks to develop a computational code capable of simulating the formation rate of different gas hydrates, under any thermodynamic conditions, exhibiting the advantage of reducing the number of experiments needed to evaluate its formation behavior. To assess the feasibility of simulating the formation of other gas hydrate compositions, the code was used to simulate the cyclopentane hydrate formation. The idealized computational model successfully performed the numerical reproduction of the experimental curves for the methane hydrate, presenting the biggest error of 19.73%. The results presented in this work are consistent with published works, providing means of observation of the initial experimental conditions influence until the final stage of formation. Furthermore, the computational code has a global nature, which allows the simulation of different gas hydrate compositions, with promising application in the development of hydrate-based technologies.